La inteligencia artificial en el periodismo: una solución al problema de la desinformación en la era digital - Castro Tomala, Cristhian Alberto (2025)
This research provides a comprehensive analysis of the potential of AI to improve journalism, while recognizing the ethical and practical challenges associated specifically in the context of Babahoyo, Ecuador. Key aspects of the thesis Contextualization: The study begins under global, national Ecuador and local Babahoyo contexts of disinformation. It highlights the challenges posed by the rapid spread of false information through digital platforms and the dual role of AI in both creating and combating it. Problem statement: This thesis questions whether AI can restore credibility in digital news or whether its misuse could further damage ethical journalism. The potential of AI to generate sophisticated false content is recognized. The main objective is to determine the role of AI in mitigating disinformation, focusing on its ability to improve the accuracy and creativity of news. The methodology employs a qualitative, non-experimental and cross-sectional design using:  Document analysis of relevant publications and news from 8 digital media outlets in Babahoyo.  Interviews with journalists and experts on the use of AI in journalism.  Observations of media coverage and narrative dynamics.